Extracellular DNA in blood products and its potential effects on transfusion. Issue 3 (25th March 2020) - Yang, Li; Yang, Dongmei; Yang, Qian; Cheng, Fu; Huang, Yuanshuai
Abstract: Blood transfusions are sometimes necessary after a high loss of blood due to injury or surgery. Some people need regular transfusions due to medical conditions such as haemophilia or cancer. Studies have suggested that extracellular DNA including mitochondrial DNA present in the extracellular milieu of transfused blood products has biological actions that are capable of activating the innate immune systems and potentially contribute to some adverse reactions in transfusion. From the present work, it becomes increasingly clear that extracellular DNA encompassed mitochondrial DNA is far from being biologically inert in blood products. It has been demonstrated to be present in eligible blood products and thus can be transfused to blood recipients. Although the presence of extracellular DNA in human plasma was initially detected in 1948, some aspects have not been fully elucidated. In this review, we summarize the potential origins, clearance mechanisms, relevant structures, and potential role of extracellular DNA in the innate immune responses and its relationship with individual adverse reactions in transfusion.